AN INSTITUTIONALIST ANALYSIS OF CURRENCY BOARDS IN ESTONIA, LITHUANIA AND ARGENTINA - Kuokštis, Vytautas; Feldmann, Magnus (Politologija, 2015)
This article analyses currency boards from the perspective of new institutionalism, namely historical institutionalism. New institutionalism holds the view that institutions have independent, autonomous effects on the social world. Once established, institutions tend to become stronger over time due to path dependency. At the same time, the new institutionalist literature has been criticized for either ignoring or not being able to properly account for institutional change. This article pays attention to both self-enforcing and self-undermining effects generated by currency boards. Furthermore, the interaction of the currency board regime with other national institutions is analysed. After laying out the theoretical arguments, this article empirically assesses them with the analysis of three cases of currency board regimes in Estonia, Lithuania, and Argentina. One of the findings is that currency boards tend to become more popular over time. This tendency can be explained by several self-enforcing effects related to growing indebtedness in foreign currencies, currency boards’ role in ensuring macroeconomic stability as well as emerging ideational consensus supporting the regime. However, currency boards also unleash self-undermining tendencies, primarily related to the increasing general indebtedness and deteriorating competitiveness. The relationship of currency boards with the broader institutional set-up proved to be important. Unlike in Lithuania and especially in Estonia, the national institutional landscape in Argentina was unfavourable for the existence of the currency board regime. This was especially evident during the economic downturn of 1998–2002 when Argentina attempted to implement the internal adjustment strategy in order to safeguard the currency board. Nevertheless, Argentina’s inability to quickly adopt a major fiscal consolidation package eventually led to the demise of the currency board regime. In turn, this inability can be attributed to the lack of informal norms of fiscal prudence, decentralized nature of Argentina’s political institutions, and the organization of interest groups. The analysis provided in this article thus suggests that, despite important self-enforcing effects of currency boards, they are not sufficient to bring about the major transformation of a generally unfavourable national institutional landscape.